Introducing Cattle Producer to the Hardin s World- Can Monopolies in Seed Markets Be Welfare Enhancing? - Sylwia Bialek (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The paper investigates markets ridden by problems of common pool resources and asks how monopoly rights for inputs into those markets affect the welfare. The analysis rests upon the example of anit-pest innovations. The quintessential feature of such innovations is the possibility of them losing their effectiveness. Their application exerts evolutionary pressure on pests that eventually leads to them devoloping resistance to the innovation. The ensuing perishability of the innovation makes its common pool resource character visible. The paper develops a model of agricultural markets and discusses how monopolies, despite their underprovision of output may lead to increased welfare compared to generic industries. In this context, the optimal patent length is investigated.
Keywords: Q58; Q16; L50; 330